A rare case of spontaneous posterior wall rupture in an unscarred uterus during labour - Nanda, Kirty; Singh, Shakun; Dhama, Vandana; Choudhary, Rachna; Azad, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine rupture is a dreaded catastroph in obstetrics with a high incidence of maternal and fetal morbidity. In developing Country, the overall prevalence widely varies from 1 in 2,000 to 1 in 200 deliveries. Uterine rupture in an unscarred uterus is a rare event and only a finger countable cased have been reported on posterior rupture of uterus in unscarred uterus. We here presenting a case of spontaneous posterior rupture of an unscarred uterus. Our patient was 38 years old grand multipara, a 6th gravida female with 4 parity, 1 abortion last year and 3 live issues. She was 9 months of gestation with previous all normal vaginal deliveries. This time she had a uterine rupture in the lower segment of posterior wall of uterus during labour. The rupture was unrepeatable, so we have to do hysterectomy. This case points out to keep this catastroph in mind in multiparas with unscarred uterus and to be prepared for the same while assisting a normal vaginal delivery.